Decision Support System for Specialization Selection Based on Student Interests and Abilities Using the Weighted Product Method - Lusiana Wulansari; Asri; Nur Azizah Muchtar (Ceddi Journal of Education, 2023)
This research was developed to provide a more efficient and accurate solution in assisting the process of selecting student specializations. This research aims to help schools determine whether or not specializations are appropriate for students. The method used in this research is the Weighted Product (WP) Method. This method was chosen because it is capable of solving multi-criteria problems and providing specialization recommendations based on accurate criteria weight calculations. Next, the data that has been collected will be entered into a decision support system that has been created using the Weighted Product method. This Decision Support System will calculate the weight scores and criteria that have been determined. It is hoped that the results of this research can help schools provide specialization options that suit students' interests and abilities. The application test results and questionnaire test results are categorized as feasible based on the research success table and implementation This decision support system application shows that this application runs well through functional testing and produces the expected output.